The leafy liverworts (Marchantiophyta) of the Valley of Mexico - Catalina Juárez-Martínez; Claudio Delgadillo-Moya (Revista Mexicana de Biodiversidad)
The leafy liverwort flora from the Valley of Mexico has been less explored than the moss flora in the same region. There are no taxonomic, floristic or phytogeographic studies for this plant group, although in the literature there are sporadic reports. This contribution records 73 species, 1 variety and 1 subspecies of leafy liverworts that occur in the Valley of Mexico based on the review of the literature and examination of herbarium specimens. Lejeuneaceae (16 species) and Frullaniaceae (12 species) are the most diverse families of the region. A key and a brief description of each taxon are provided. Thirty one species recorded in the literature and/or found in herbarium collections at MEXU were not found in the field. Environmental degradation, lack of collecting in inaccessible areas, and inaccurate or incorrect data collection may account for their current absence.